Occupation, Religion, and the Voidable Politics of Empire at the US-Mexico Border - Lugo, Alejandro (Religion and society, 2015)
Following Ann Stoler's analysis of "imperial debris" and Gastón Gordillo's notion of the "void", this article examines how, in the context of the Mexican-American War of 1846–1848, imperial and religious impulses have endured from the mid-nineteenth century to the present at the US-Mexico border. Using photographs taken at different "sites of memory" located along the 60-mile corridor that connects Las Cruces, New Mexico, with El Paso, Texas, this analysis demonstrates that the continuing American occupation of Mexican lands has contributed to the oblique inclusion and parallel exclusion or erasure of the historical presence of the Mexican community, as well as its political, cultural, and historical legitimacy in the region. However, the essay argues that ultimately the "voidable" status of the American presence in the US-Mexico border region continues to reproduce itself. The article closes with a series of photographs of churches that capture religious landscapes that manifest, challenge, and transcend the occupied borderlands through the materiality of their presence.